Dos rios à tela de cristal líquido: o retorno do mito e a arquitetura da cultura convergente em League of Legends - MACEDO, Tarcízio Pereira (Universidade do Vale do Rio dos Sinos, 2022)
This paper seeks to weave an analysis about the online game known as League of Legends, understanding it as a contemporary cultural product and a transmedia world, with the possibility of tracing a path of competitive games, often taken with a predominance of competition (agôn), as vectors of a meaningful narrative. In this sense, we try to identify some phenomena of the so-called convergent architecture culture in the game from the creation of a skin based on Amazon Iara. Thus, we present the history, the functioning and the relationships that the game and its transmidiatic products have with the global consumer culture, as well as their strategies in order to attract consumers to a virtual environment, promoting participatory culture, the reframing and the return of the myth in contemporary societies.